2007
DOI: 10.1002/tie.20166
|View full text |Cite
|
Sign up to set email alerts
|

Managing international strategic alliance relationships

Abstract: The objective of this study is to investigate the development of international strategic alliances (ISAs) and to identify the important factors for each phase of an alliance relationship. We have developed a framework about the process development of alliances that is based on an extensive literature study. The framework is used to study and analyze three cases of ISAs. The findings and conclusions are presented in a manner that can help managers to recognize the stages they have to go through and, more import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
1
17
0
1
Order By: Relevance
“…In an R&D alliance, determining the alliance scope provides an alternative way to prevent knowledge leakage and protect technological assets (Oxley & Sampson, ). This is critical for risk management (Wahyuni, Ghauri, & Karsten, ). It has been shown that determining alliance scope is “one of the most important tasks the partners will undertake.…”
Section: Empirical Approach: Sample and Description Of The Biopharmacmentioning
confidence: 99%
“…In an R&D alliance, determining the alliance scope provides an alternative way to prevent knowledge leakage and protect technological assets (Oxley & Sampson, ). This is critical for risk management (Wahyuni, Ghauri, & Karsten, ). It has been shown that determining alliance scope is “one of the most important tasks the partners will undertake.…”
Section: Empirical Approach: Sample and Description Of The Biopharmacmentioning
confidence: 99%
“…With the increasing number of multinational companies and international alliances, understanding the cross‐cultural differences and institutional framework of the host country in conflict management has become increasingly important (Brett, Tinsley, Shapiro, & Okumura, ; Holt & DeVore, ; Kozan, ; Tinsley & Brett, ; Wahyuni, Ghauri, & Karsten, ; Seyoum, ). As many businesspeople have discovered, ineffective negotiations and poor conflict management often contribute to problematic international operations (Adler, ; Brett et al, ; Gammelgaard, Kumar, & Worm, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nesse sentido, a adoção de estratégias cooperativas tem se tornado, há algum tempo, cada vez mais comum entre organizações em todo o mundo (Schifrin, 2001). Nesse contexto, a compreensão do seu funcionamento é de grande valia para a administração contemporânea, o que tem levado diversos autores a pesquisarem sobre o tema (Beamish, 1985;Powel, 1987;Contractor e Lorange, 1988;Hennart, 1988;Borys e Jeminson, 1989;Kogut, 1991;Osborn e Hagedoorn, 1997;Child e Faulkner, 1998;Gulati, 1998;Rodrigues, 1999;Hitt e Dacin, 2000;Wahyuni et al, 2007;Agarwal et al, 2010).…”
Section: Introductionunclassified